2009
DOI: 10.1074/jbc.m109.015339
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Mutagenesis of α-Conotoxin Vc1.1 Reveals Residues Crucial for Activity at the α9α10 Nicotinic Acetylcholine Receptor

Abstract: Vc1.1 is a disulfide-rich peptide inhibitor of nicotinic acetylcholine receptors that has stimulated considerable interest in these receptors as potential therapeutic targets for the treatment of neuropathic pain. Here we present an extensive series of mutational studies in which all residues except the conserved cysteines were mutated separately to Ala, Asp, or Lys. The effect on acetylcholine (ACh)-evoked membrane currents at the ␣9␣10 nicotinic acetylcholine receptor (nAChR), which has been implicated as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
122
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 79 publications
(134 citation statements)
references
References 42 publications
11
122
1
Order By: Relevance
“…It is likely that the proline residue in PeIA will also be critical for activity, but this probably derives from a structural, rather than functional, role of this residue. Previous studies have shown that when this proline is mutated to alanine in Vc1.1, significant perturbations in structure are observed (23). Furthermore, we recently showed that a naturally occurring ␣-conotoxin, LtIa, which does not contain this conserved proline, does not have a well defined structure in solution (32).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is likely that the proline residue in PeIA will also be critical for activity, but this probably derives from a structural, rather than functional, role of this residue. Previous studies have shown that when this proline is mutated to alanine in Vc1.1, significant perturbations in structure are observed (23). Furthermore, we recently showed that a naturally occurring ␣-conotoxin, LtIa, which does not contain this conserved proline, does not have a well defined structure in solution (32).…”
Section: Discussionmentioning
confidence: 99%
“…Mutagenesis studies on Vc1.1 (23) and RgIA (31) have shown that the Asp-Pro-Arg motif in loop 1 is crucial for activity at the ␣9␣10 nAChR. However, in PeIA, the equivalent residues are His-Pro-Ala, yet it remains a potent antagonist of the ␣9␣10 nAChR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scanning mutagenesis of ␣-conotoxin Vc1.1 revealed that Ser4 and Asn9 are important for ␣9␣10 nAChR potency (Halai et al, 2009), whereas for RgIA, Asp5, Pro6, and Arg7 were shown to be critical for both ␣9␣10 and ␣7 nAChR blockade (Ellison et al, 2008). It is noteworthy that these ␣9␣10-selective ␣-conotoxins are analgesic in different animal models of chronic pain, but there is an uncertainty about the true molecular target responsible for this effect.…”
Section: A Conotoxin Inhibitors Of Nicotinic Acetylcholine Receptorsmentioning
confidence: 99%
“…Therefore, the different subtype specificities of Vc1.2 and Vc1.1 for nAChR binding must arise from the specific amino acid side chain differences in these toxins. Amino acid residues affecting the affinity of Vc1.1 for the ␣9␣10 subtype were determined by scanning mutagenesis (54 55)) indicating that changes in these side chains may abolish binding to these nAChR subtypes (Fig. 5).…”
Section: Identification Of Novel Conotoxin Transcripts In C Victoriaementioning
confidence: 99%